Antibiofilm Activity of Bacteriophage Isolated from Sewage-Polluted Water against Escherichia coli (Tribhuvan University Journal of Microbiology, 2025)
Objectives: This study aimed to explore bacteriophages, viruses that infect bacteria, as an alternative antibiofilm agent.Method: A laboratory-based, cross-sectional study was conducted at the Sainik Awasiya Mahavidyalaya Laboratory from February to July 2025. The water samples that were contaminated with effluents were collected from eight rivers and ponds across the Kathmandu valley. E. coli isolates were used as the host strain after being confirmed by biochemical tests. Phages were isolated and enriched from wastewater using centrifugation, filtration, and multiple cycles of incubation with log-phage host bacteria to gain high titres. The plaque assay, host range by spot assay, and Efficacy of Plating (EOP) were performed. Antibiofilm activity was evaluated using the microtiter plate crystal violet assay. The study compared biofilm formation in the isolated E. coli (E.C 8) with that of the standard E. coli (ATCC 8739). Statistical significance was determined using the t-test (p ≤ 0.05).Results: Bacteriophages were found in six of eight samples. Only Mulpani had a lytic phage with a titre of 7.5 PFU/ml, which was used for further testing. The phage exhibited moderate EOP, ranging from 0.28 to 0.60, and a moderate host range. The isolated phage showed selected antibiofilm activity, as it effectively reduced the biofilm of the isolated E. coli (22.8%).Conclusion: This emphasizes the ability of lytic phages as antibiofilm agents.